Continuous time series analysis on the effects of induced running fatigue on leg symmetry using kinematics and kinetic variables: Implications for knee joint injury during a countermovement jump - Gao, Zixiang; Zhao, Liang; Fekete, Gusztáv; Katona, Gábor; Baker, Julien S.; Gu, Yaodong (Frontiers in Physiology, 2022)
This study investigates the symmetry change in joint angle and joint moment of knee joints following a Running-Induced Fatigue countermovement Jump. Twelve amateur runners were recruited for the study to perform the Countermovement Jump test. During the push-off and lending stage, joint angle and moment were recorded pre- and immediately posted fatigue. The prolonged-running protocol was used to induce fatigue. Symmetry function (SF) was used to assess the symmetry of the knee Angle and moment variation parameters over the entire push-off and lending phases based on time series analysis. Paired sample T-test was used to examine changes in SF before and after acute fatigue. The Angle and moment of the knee are asymmetrical in all planes (SF>0.05), with SF ranging from 5% to 130% in angles and 5% to 110% at the moment. There was a significant increase in knee joint angle asymmetry in the horizontal plane during the push-off and lending stage following the prolonged - Running Protocol implementation. These findings provide evidence for unilateral knee injury caused by running fatigue during jumping tasks. In performance related tasks, the risk of injury to the dominant knee joint should be a cause for concern for coaching staff and shoe manufacturers.